The challenges of keeping clinicians unaware of their participation in a national, cluster-randomised, implementation trial - Jex Kuo; Sonja Woodall; Jane Harding; Caroline Crowther; Jane Alsweiler (BMC Medical Ethics, 2022)
Abstract Background Implementation of recommendations from clinical practice guidelines is essential for evidence based clinical practice. However, the most effective methods of implementation are unclear. We conducted a national, cluster-randomised, blinded implementation trial to determine if midwife or doctor local implementation leaders are more effective in implementing a guideline for use of oral dextrose gel to treat hypoglycaemic babies on postnatal wards. To prevent any conscious or unconscious performance bias both the doctor and midwife local implementation leaders were kept unaware of the trial. This paper reports the ethical dilemmas and practical challenges of ensuring clinicians remained unaware of their involvement in an implementation trial. Methods We sought approval from the National Health and Disability Ethics committee to keep clinicians unaware of the trial by waiving the standard requirement for locality approval usually required for each district health board. The ethics committee did not approve a waiver of consent but advised that we approach the chief executive of each district health board to ask for provisional locality approval. Ultimately it was necessary to seek ethics approval for three separate study designs to keep clinicians unaware of the trial. Results The median (IQR) time for chief executive approval was 16 (6–40) days and for locality approval was 57 (39–84) days. We completed 21 different locality approval forms for 27 hospitals. Conclusions Keeping clinicians unaware of their involvement in a national implementation cluster-randomised trial is feasible. However, despite a national ethics committee, significant logistical challenges were time consuming and delayed trial completion. Co-ordination of the locality approval process would help facilitate multi-centre trials.